2000
DOI: 10.1093/tropej/46.3.132
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic scoring method for the assessment of the severity of nutritional rickets

Abstract: Radiographic changes of rickets are well characterized, but no method of grading the severity of these changes has been in general use. Consequently, it is difficult to compare objectively or follow radiographic improvement. We prospectively evaluated the utility and reproducibility of a scoring method for measuring the severity of rickets. A 10-point score for radiographs of wrists and knees was devised to assess the degree of metaphyseal fraying and cupping and the proportion of the growth plate affected. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(144 citation statements)
references
References 0 publications
2
139
0
3
Order By: Relevance
“…Outcome assessments. The primary endpoint objective, evaluation of changes in the skeletal manifestations of hypophosphatasia (see Supplemental Methods), was obtained using the RGI-C (9) and RSS (20). The RGI-C, a 7-point ordinal scale, assesses hypophosphatasia skeletal disease in wrists and knees, including physeal widening, irregularity of the provisional zone of calcification, metaphyseal flaring, radiolucencies, and patchy osteosclerosis, as well as recent fractures (see Supplemental Methods) (9).…”
Section: Methodsmentioning
confidence: 99%
“…Outcome assessments. The primary endpoint objective, evaluation of changes in the skeletal manifestations of hypophosphatasia (see Supplemental Methods), was obtained using the RGI-C (9) and RSS (20). The RGI-C, a 7-point ordinal scale, assesses hypophosphatasia skeletal disease in wrists and knees, including physeal widening, irregularity of the provisional zone of calcification, metaphyseal flaring, radiolucencies, and patchy osteosclerosis, as well as recent fractures (see Supplemental Methods) (9).…”
Section: Methodsmentioning
confidence: 99%
“…The methodology used does not support any determination of whether these associations may have been causal. Rickets in Chakaria appears to be of the Ca deficiency type that has been documented in South Africa (Pettifor et al, 1978) and Nigeria (Okonofua et al, 1991;Oginni et al, 1996;Thacher et al, 1997Thacher et al, , 1999Thacher et al, , 2000a. It is significant that Chakaria is not regarded as among the poorest areas of Bangladesh, and that the level of malnutrition, including Ca undernutrition, among at-risk children in Chakaria is not substantially different from that of children living elsewhere in Bangladesh where rickets is not endemic.…”
Section: A Priori Hypothesesmentioning
confidence: 95%
“…It tends to be thought of in historic terms, without the recognition in many quarters that it continues to be a source of disability in the developing world. In recent years, rickets has been reported in some 21 countries (Bishop, 2001), including Tibet (Harris et al, 2001), Kuwait (Majid Molla et al, 2000), Ethiopia (Muhe et al, 1997), Yemen, (Banajeh et al, 1997), Mongolia (Fraser & Tserendolgor, 2001), the United Kingdom (Mughal et al, 1999), the United States (Eugster et al, 1996;Pugliese et al, 1998;Kreiter et al, 2000;Shah et al, 2000), South Africa (Pettifor et al, 1978), Nigeria (Okonofua et al, 1991;Oginni et al, 1996;Thacher et al, 1997Thacher et al, , 1999Thacher et al, , 2000a, and Bangladesh (Snedecor & Cochran, 1967;Anonymous, 1998;Fischer et al, 1999;Staab et al, 1999;Karim et al, 2001). While some of these reports describe sporadic occurrences of the disease in association with lifestyle and the lack of solar exposure sufficient to support adequate vitamin D biosynthesis, studies in South Africa (Pettifor et al, 1978) and Nigeria (Okonofua et al, 1991;Oginni et al, 1996;Thacher et al, 1997Thacher et al, , 1999Thacher et al, , 2000a have shown the disease to be caused by primary dietary deficiencies of calcium (Ca).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst this might be evident on radiographs, it is highly subjective [72], and there is little objective evidence to demonstrate mineralisation defects in children with clinical rickets. Three studies have measured bone mineralisation by DXA in children diagnosed with VDD rickets.…”
Section: Vitamin D and Bone Mineralisation Bone Mineral Density In Vimentioning
confidence: 99%